Economic impact analysis of coffee enterprises on community income in Mimika Regency, Central Papua Province - Kristina Maria Pek; J. Ary Mollet; Transna Putra Urip (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study analyzes the economic impact of independent coffee enterprises on household income and local diversification in Mimika Regency, Central Papua, where dependence on mining remains dominant. Research/methodology: A mixed-methods approach was applied, combining a survey of 120 respondents with 30 in-depth interviews involving farmers, cooperatives, traders, and government officials. Primary data were collected through questionnaires, interviews, and field observations, while secondary data came from BPS reports and cooperative records. Quantitative analysis used descriptive statistics, correlation, and regression, while qualitative data were thematically analyzed with Atlas.ti. Results: The findings show that coffee enterprises significantly increase household income, with over 68% of respondents reporting growth of 15–25%. Statistical tests confirm a strong correlation between coffee enterprise activities and household welfare. However, their contribution to job creation remains limited, as most enterprises operate on a micro scale and rely on family labor. Structural barriers, including limited capital, poor infrastructure, weak branding, and market constraints, hinder expansion. Despite these challenges, coffee enterprises hold strong potential as alternative drivers of local economic diversification beyond mining. Conclusions: Independent coffee enterprises positively impact household income but have yet to create significant employment opportunities. Strengthening access to finance, infrastructure, and marketing is essential to maximize their role in sustainable regional development. Limitations: The study is limited to Mimika Regency and small-scale enterprises, which may not reflect broader regional dynamics. Contribution: This research contributes empirical evidence on coffee’s role in economic diversification in resource-dependent regions and offers policy insights to support sustainable development strategies in Central Papua.